2007
DOI: 10.1002/anie.200702751
|View full text |Cite
|
Sign up to set email alerts
|

Alternate‐Site Enzyme Promiscuity

Abstract: Promiscuous reactions get around: It is shown that promiscuous enzyme‐catalyzed reactions (i.e., the catalysis of distinctly different chemical transformations) can also take place at sites other than where the natural reaction occurs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(18 citation statements)
references
References 48 publications
(11 reference statements)
1
17
0
Order By: Relevance
“…Therefore, it appears that the gene family model described for FLS, with one catalytically active member and several pseudogenes, may also apply to other flavonoid genes, particularly in the case of CHI. There is also a growing awareness that the ''promiscuity'' of metabolic enzymes such as ANS, as well as flavonoid glycosyltransferases (Lim et al, 2004) and O-methyltransferases (Deavours et al, 2006), is more the rule than the exception (Taglieber et al, 2007). These ''alternative'' functions of otherwise well-characterized proteins may represent new paradigms that must be taken into account in efforts to develop framework models of cellular metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it appears that the gene family model described for FLS, with one catalytically active member and several pseudogenes, may also apply to other flavonoid genes, particularly in the case of CHI. There is also a growing awareness that the ''promiscuity'' of metabolic enzymes such as ANS, as well as flavonoid glycosyltransferases (Lim et al, 2004) and O-methyltransferases (Deavours et al, 2006), is more the rule than the exception (Taglieber et al, 2007). These ''alternative'' functions of otherwise well-characterized proteins may represent new paradigms that must be taken into account in efforts to develop framework models of cellular metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…An apparent value for the enantioselectivity (E app ) in the hydrolysis of 3-bromo-2-methylpropionate was estimated as ca. 41. It was further shown that 2-bromopropionate inhibited the esterase activity and that p-nitrophenyl butyrate inhibited the haloacid dehalogenase activity.…”
Section: ) Activitymentioning
confidence: 95%
“…perform catalysis at an alternative active site (enzyme alternate-site promiscuity). [40,41] The phenomenon of enzyme catalytic promiscuity in the field of biocatalysis has been highlighted in several review articles. [40,[42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59] …”
Section: Enzyme Promiscuity Different Types Of Enzyme Promiscuitymentioning
confidence: 99%
“…It constitutes a very important property of many enzymes, having a natural role in evolution and, occasionally, in the biosynthesis of secondary metabolites. [1][2][3][4][5][6][7] For example, it has been demonstrated that vanadium-dependent chloroperoxidase shows phosphatase activity when vanadate is not present, indicating that its active site is very similar to that of the acid phosphatases. 8 On the other hand, it was found that an acid phosphatase from plants (in contrast to the kidney bean purple acid phosphatase (PAP)) uniquely exhibits chloroperoxidase activity with loss of phosphatase activity when orthovanadate is added to the apo form of the enzyme.…”
Section: Introductionmentioning
confidence: 99%
“…11,12 Nevertheless, no catecholase activity for any of the well characterized PAPs has as yet been described. While several enzymes displaying catalytic promiscuity have been the subject of recent related investigations, [1][2][3][4][5][6][7] there are few examples of synthetic analogues which exhibit such multifunctional activities. [13][14][15][16][17][18] In recent years, considerable attention has been devoted to the synthesis, X-ray structural analysis and physicochemical characterization of structural and functional dinuclear Fe III M II mimetics for the active site of metallohydrolases such as purple acid phosphatase.…”
Section: Introductionmentioning
confidence: 99%